Balancing Significance and Maintaining 'Sense of Place' in the Sustainable Display of Tudor Tapestries in the Great Hall, Hampton Court Palace. (1st August 2018) - Frame, Kate; Vlachou-Mogire, Constantina; Hallett, Kathryn; Takami, Mika
ABSTRACT: Hampton Court Palace's Great Hall located in Surrey, UK, is a magnificent late medieval hall. Its large hammer-beam roof is sumptuously decorated while its walls for the past century have been rehung with Henry VIII's five-hundred-year-old tapestries illustrating The Story of Abraham, and one of the most internationally significant sets of sixteenth-century tapestries, commissioned for the same hall. This paper presents research which began in 2007, exploring conservation solutions based on evidence-based decision-making, through to successful implementation of measures that conserve these invaluable tapestries without damaging the aesthetic or physical integrity of the Great Hall. The impacts of environmental exposure conditions mapped in detail were assessed to evaluate risk for each tapestry. Next, feasibility studies identified the effectiveness of a range of potential mitigating options to address each local risk, now being incrementally implemented over many years. The research has enabled us to develop, test and deliver permanent interventions that have – when considered together as a holistic management regime – allowed the tapestries to remain in situ . These interventions will continue to be monitored and evaluated for at least a further year to confirm their effectiveness.